Table of Content - - (Journal of Curriculum and Teaching Methodology, 2023)
Table of Content:1. Kindergarten teachers practice in Hafar Al-Batin for active learning strategiesMrs. Ghada Ahmed Aljurbua2. The Effectiveness of A Teaching Program Based on Some of Principles of TRIZ Theory for Teaching Science in The Development of Reflective Thinking Skills at The 2nd Intermediate Grade StudentsMr. Waleed Saleh Alzaidi , Prof. Naif Abdulaziz Almutawa3. The role of the Islamic education teacher in developing the values of moderation and moderation among secondary school students in JeddahMr. Fahad Ahmed Alomari , Prof. Habba Ahmed Akram4. Effect of Employing Micro-Learning in an E-learning Environment on Correcting Spelling Errors Among Middle School StudentsMrs. Al-Jawhara Naif Al-Shaibani , Co-Prof. Abdellraouf Mohamed Mohamed Ismail5. Models and Strategies when Effective use of Electronic Games in Teaching English VocabularyDr. Afrah Haft Alawaty , Mrs. Somaya Suleiman Abu Zahra6. A proposal to Add a Scholarship Unit for Islamic Education Curriculum for third Secondary Students According to Schools Promoting Positive Behavior in View of the Kingdom's Vision 2030Mrs. Najwa F. Idrees7. The Effectiveness of Rotation of Stations Model for Blended learning in Developing the Creative Thinking Skill "Evaluating and Improving Ideas" in the Light of the PISA Framework for Mathematics Among Second- Grade StudentsMrs. Amerh Owud Onallah Alsulmi
Keywords: Journal of Curriculum and Teaching Methodology